Laser surgery as a management option for twin anemia–polycythemia sequence. (4th August 2014) - Slaghekke, F.; Favre, R.; Peeters, S. H. P.; Middeldorp, J. M.; Weingertner, A. S.; van Zwet, E. W.; Klumper, F. J.; Oepkes, D.; Lopriore, E.
ABSTRACT Objective To evaluate the effectiveness of laser treatment for antenatally detected twin anemia–polycythemia sequence (TAPS) compared with intrauterine transfusion or expectant management. Methods All monochorionic twin pregnancies with TAPS managed between 2005 and 2013 in two European fetal therapy centers were evaluated. The outcomes of TAPS cases treated primarily with laser surgery were compared with the outcomes of cases managed expectantly or treated with intrauterine transfusion. Results In this retrospective study 52 cases of TAPS were detected antenatally and were managed with either laser surgery (n = 8; 15%) or intrauterine blood transfusion (n = 17; 33%) or expectantly (n = 27; 52%). Perinatal survival in the laser group was 94% (15/16) vs 85% (29/34) in the intrauterine‐transfusion group and 83% (45/54) in the expectant‐management group (P = 0.30). The rates of severe neonatal morbidity in liveborn neonates in the laser, intrauterine‐transfusion and expectant‐management groups were 7% (1/15), 38% (12/32) and 24% (12/50), respectively (P = 0.17). There was a significant reduction in respiratory distress syndrome in cases treated by laser. No severe postnatal hematological complications were detected in the laser group compared with 72% (23/32) in the intrauterine‐transfusion group and 52% (26/50) in the expectant‐management group (P < 0.01). Median time between diagnosis and birth was 11 weeks in the laser group compared to 5 weeks after intrauterine transfusion and 8 weeks after expectant management (P < 0.01). After injection of colored dye no residual anastomoses were found in the laser group. Conclusions Laser surgery for TAPS appears to improve perinatal outcome by prolonging pregnancy and reducing respiratory distress syndrome. Larger, adequately controlled studies are needed to reach firm conclusions on the optimal management of TAPS. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd